T-Lymphocyte Subsets Alteration, Infection and Renal Outcome in Advanced Chronic Kidney Disease - Xiong, Jiachuan; Qiao, Yu; Yu, Zhikai; Huang, Yinghui; Yang, Ke; He, Ting; Zhao, Jinghong (Frontiers in Medicine, 2021)
Background: T-lymphocyte subsets reflect patients' immune status and are associated with adverse outcomes in various diseases. However, the association between T-lymphocyte subsets and major infection and renal outcome in chronic kidney disease (CKD) patients has not been well addressed. Methods: Patients diagnosed with stage 3-5 of non-dialysis CKD were recruited and healthy subjects were selected as the controls. T-lymphocyte subsets (CD3+, CD4+, CD8+) were detected by flow cytometry, and the CD4+/CD8+ T cell ratio was then calculated. Patients were divided into the normal-level group and the low-level group according to the clinical reference value. The primary outcomes were the major infection and renal outcome. Results: A total of 410 CKD patients were enrolled; the average age was 47.25 years. Compared to the healthy controls, the level of CD3+, CD4+, CD8+ T cells, and the CD4+/CD8+ T cell ratio were significantly decreased in CKD patients (p<0.05). During the median follow-up of 2.56 (quartile interval 1.24 to 3.46) years, major infections occurred in 15.10% of the CKD patients. The incidence of infection was significantly higher in the low-level group of CD3+, CD4+ T cells, and CD4+/CD8+ T cell ratio compared with the normal level groups. Kaplan-Meier analysis showed that the lower level of CD3+, CD4+ T cells, and CD4+/CD8+T cell ratio is associated with a greater risk of infection. Cox regression analysis further confirmed and low CD3+, CD4+ T cells, and CD4+/CD8+ T cell ratio were independent risk factors of infection in CKD patients. Moreover, during the follow-up, renal events occurred in 37.50% of patients. Kaplan-Meier analysis indicated that low levels of CD3+, CD4+, and CD8+ T cells are significantly associated with renal outcome in CKD patients, Cox regression analysis showed that low level of CD3+ T cells (HR=2.407, 95%CI:1.664-3.482, p<0.001), CD4+ T cells (HR=2.397, 95%CI: 1.633-3.518, p<0.001) and CD8+ T cells (HR= 2.416, 95%CI: 1.476-3.955, p<0.001) were independent risk factors for renal outcome after multivariable-adjusted. Conclusion: CKD patients had a defect in T-lymphocyte subpopulation. T-lymphocyte subsets were closely associated with infection and renal outcome in CKD patients. suggesting T-lymphocyte subsets are independent predictors of infection and renal outcome in CKD patients.